2018
DOI: 10.1002/jcad.12227
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Wellness in Refugee Populations

Abstract: Refugee populations experience risk factors that may influence their wellness. As the number of refugees continues to rise, it is important for professional counselors, counselor educators, and counselors‐in‐training to be aware of techniques for supporting wellness in this population. This article addresses risk factors to refugee wellness within the indivisible self model of wellness (Myers & Sweeney, ) and highlights current wellness trends and the importance of a prevention‐based treatment paradigm for hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Some countries, where refugee food insecurity are already echoing in public health priorities, have begun strategies for reducing food insecurity, supplementation, food fortification, or new food and nutrition education tools, like cooking classes and food workshops for refugees 41 . Malnutrition is closely related to the onset of chronic diseases, and health promotion and prevention tools are indispensable for use with vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries, where refugee food insecurity are already echoing in public health priorities, have begun strategies for reducing food insecurity, supplementation, food fortification, or new food and nutrition education tools, like cooking classes and food workshops for refugees 41 . Malnutrition is closely related to the onset of chronic diseases, and health promotion and prevention tools are indispensable for use with vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the A9 study it was pointed out that of the 2,501 families participating in the study, 55% had food insufficiency, 62% presented food insecurity, and also showed that households with residents with a disability (of known cause) had more reports of insufficient food, variation and severe food insecurity. The A12 study, conducted with 2,575 Palestinian refugee families, points to 41% (CI: [39][40][41][42][43] and 20% (CI: 18-22) of Palestinian refugees experiencing moderate and severe food insecurity respectively. This study also shows the relation between food insecurity with poverty, unemployment, and some chronic illness or disability.…”
Section: Food Inequitymentioning
confidence: 99%
“…For example: Introduction and ethics coursework may emphasize wellness as foundational to counselor identity and essential self‐advocacy practices to prevent burnout and impairment (Dang & Sangganjanavanish, 2015), concerns likely exacerbated during the COVID‐19 pandemic. Assessment courses may utilize the 5F‐Wel (Myers & Sweeney, 2005c), to explore their own wellness while learning how to conduct, interpret, and plan interventions with a well‐researched instrument consistent with counseling principles and practices. Group, techniques, and relationship counseling courses may train students in cross‐dimensional strengths facilitation practices (Orht et al., 2019). Practicum, internship, and supervisor training courses may utilize wellness supervision models such as the Wellness Model of Supervision (Lenz & Smith, 2010). Multicultural and theories counseling may explore the relationships between wellness models (e.g., Indivisible Self) and multicultural and social justice counseling practices (Blount & Acquaye, 2018; Ivey et al., 2012; Prilleltensky, 2012). As the world emerges from the pandemic and continues to grapple with entrenched racism and injustices, the relevance of wellness is as important now as ever, all of which provides direct relevance in the classroom. …”
Section: Implications For Counselor Educationmentioning
confidence: 99%
“…Post settlement health initiatives often classify all refugee communities as one homogenous group. This is misleading and can be the cause of low success rates and uptakes of health programs by different refugee groups (Kercood and Morita-Mullaney, 2015;Tyrrell et al, 2016;Ahmed, 2018;Blount and Acquaye, 2018;Wallerstein et al, 2019). Ethnographic studies with people from Burma describe them as gentle and polite, rarely asking any questions or drawing attention to themselves, and answering everything in the affirmative (Barron, 2007;Asian and Pacific Islander American Scholarship Fund, 2014;Culturalatlas.sbs.com.au, 2020).…”
Section: Introduction Backgroundmentioning
confidence: 99%